Fate of protozoa during the start-up of a sequencing batch biofilm reactor used for the degradation of hydrocarbons - Rodrigues, A. C. (2000)
Large amounts of oily sludges are retained in patrol stations by gravity interceptors in order to prevent their discharge in surface waters. Those residues are mainly composed of a mixture of hydrocarbons, water and inert solids. Therefore, their final disposal represents a significant environmental problem. This work concerns the study of microfauna biomass during the start-up of a SBBR designed for the treatment of hydrocarbon slurries retained in an API oil separator. The findings of this study suggest that protozoal colonization of the SBBR followed the same pattern of activated sludge systems, the free swimming and crawling ciliates, and also fagellates being the dominant protozoa group during the star-up period of the reactor. When the plant performance dropped, the number of flagellated protozoa rapidly increased, and a concomitant decrease in the ciliated population was observed.